2013
DOI: 10.1177/1740349913515202
|View full text |Cite
|
Sign up to set email alerts
|

Laser-induced solution synthesis and deposition: A generic method to make metal chalcogenide nanotubes at high rate with high consistency

Abstract: This article reports a new processing method for manufacturing nanotubes and possibly other nano entities with consistency at high rate. We show that this method can be applied for a wide range of materials, as demonstrated by a variety of metal chalcogenides. The proposed novel laser-induced solution synthesis and deposition method is a quantum jump for improving the consistency and manufacturing rate of chemical bath deposition and electroless deposition. We demonstrate the generic nature of this method by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Previous studies showed that it was feasible for a great variety of nanomaterials to be produced efficiently through solution-based reactions. SnO 2 , Fe 3 O 4 , MnO 2 , ZnS, etc., were successfully deposited by a pulsed-laser method in previous studies. Conventional nanomaterial synthesis methods, such as chemical vapor deposition or hydrothermal reaction, usually show a low growth rate. For example, the typical growth rate of ZnO in a hydrothermal process is in the range of a few hundred nanometers per hour. The growth rate in vapor depositions could reach a few nanometers per second, but it usually requires high temperature which demands a well-controlled environment that is not always compatible with other nanofabrication processes.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that it was feasible for a great variety of nanomaterials to be produced efficiently through solution-based reactions. SnO 2 , Fe 3 O 4 , MnO 2 , ZnS, etc., were successfully deposited by a pulsed-laser method in previous studies. Conventional nanomaterial synthesis methods, such as chemical vapor deposition or hydrothermal reaction, usually show a low growth rate. For example, the typical growth rate of ZnO in a hydrothermal process is in the range of a few hundred nanometers per hour. The growth rate in vapor depositions could reach a few nanometers per second, but it usually requires high temperature which demands a well-controlled environment that is not always compatible with other nanofabrication processes.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the output of regression analysis, the fitted lines with least sum of square for models 1 and 2 are shown in Eqs. (9) and (10). Different from sample 1, the R square improves from 0.9936 to 0.9940 when adding coating thickness as explanatory variable.…”
Section: Regression Model For Nano-indentation Test Based On Figs 5mentioning
confidence: 83%
“…Such advantages make the laser-induced chemical solution synthesis attractive and environmentally friendly. This innovative process [7,8] is scalable [9], generic [10], and capable of producing a significant improvement in the material performance [11]. It can greatly aid the development of nanostructured materials for a myriad of applications [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Developing high rate nanomanufacturing processes along with low processing temperature, large area, and non-toxicity is of great importance for industrial applications. Economical production methods need to be developed so that the huge potential of nanomaterials with novel properties can be widely used [1][2][3]. Industrial synthesis of multiwall carbon nanotube at large scale with high production rate, reduced waste, and low cost in 1980s paved the way for the widespread carbon nanotube research and applications in the past two decades [4].…”
Section: Introductionmentioning
confidence: 99%